Efektivitas Akupresur Pada Titik Perikardium 6 Terhadap Emesis Gravidarum Pada Ibu Hamil Di Klinik Arsy Medika Desa Cikalahang Kecamatan Dukupuntang Kabupaten Cirebon Tahun 2024 - Nisa Rizki Nurfita; Diani Magasida; Sri Ayu Kurnia; Nunung Nurjanah (Jurnal Kesehatan Mahardika, 2025)
Nausea and vomiting in pregnant women in Indonesia reach 14.8%. Complaints of nausea and vomiting occur in 60-80% of primigravidas and 40-60% of multigravidas. The impact of excessive nausea and vomiting in pregnancy causes hyperemesis gravidarum which results in abortion, anemia, LBW, premature labor and IUGR. Acupressure of the P6 point can stimulate the nerves to reduce emesis gravidarum. Pressure on the P6 point sends signals to the brain, balances neurotransmitters, and suppresses the gag reflex naturally. The aim of this study was to determine the effectiveness of acupressure in reducing emesis gravidarum at the Arsy Medika Clinic. The method used in the research is an experimental study design with post-test only design with control group. Sampling was taken using purposive sampling. The results of the study using statistical tests with the Mann Whitney test obtained a P value of 0.001 (< 0.005), which means that there is effectiveness of acupressure at pericardium point 6 against emesis gravidarum in pregnant women at the Arsy Medika Clinic. Acupressure on pericardium point 6 affects the intensity of nausea and vomiting in pregnant women